Tindak Pidana Penyalahgunaan Narkotika oleh Remaja di Kabupaten Gianyar - Luh Ketut Ayu Andayani; Anak Agung Sagung Laksmi Dewi; Luh Putu Suryani (Warmadewa Press, 2021)
The increase in the use of narcotics has recently shown a higher number. This creates problems for both the general public and individuals. The actions of drug abusers are very disturbing, starting from the family environment to the surrounding environment. As a result, many children are physically and mentally damaged. Of course, this will greatly affect their future. This study aims to examine the legal regulations for the criminal act of narcotics abuse by adolescents in Gianyar Regency and examine the judge's considerations in imposing criminal sanctions on narcotics abusers in Gianyar Regency. This research was designed using normative legal research with a statutory approach and a conceptual and problem approach. The data used were primary and secondary legal data. The data were obtained through field research using note-taking and documentation techniques. Furthermore, the data were analyzed descriptively qualitatively. The results showed that the application of material criminal law by the judge in case Number 516/Pid.Sus/2015/PN.Mks was fitting with the fulfillment of the elements of Article 127 Paragraph (1) letter a of Law Number 35 of 2009 concerning Narcotics by declaring the defendant legally and convincingly guilty of committing a crime of narcotics abuse. The judge's legal considerations in deciding the case Number 516/Pid.Sus/2015/PN.Mks were appropriate based on normative and sociological juridical considerations and by looking at valid evidence